(Trying to) catch up with the higher-skilled Joneses: student loans in a segmented educational market from a post-Keynesian perspective - Serra, Gustavo Pereira [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2025)
This paper analyzes the economic effects of student loans in a segmented educational market. The motivation here draws upon some studies that verify differences in labor income returns and repayment difficulties depending on the characteristics of the institution attended by the student. I put forward a neo-Kaleckian model that considers three types of households: rentiers (RHs), lower-skilled workers (LSWs), and higher-skilled workers (HSWs). Moreover, a cost-minimizing representative firm combines physical capital and labor in effective units in the production process, which also features some labor skill substitution, thus generating a bargaining process between the different worker groups over the wage gap. The main result is that, for a debt-financed human capital investment, the conditions that drive long-term economic growth do not necessarily align with those that reduce the wage gap and household debt. In fact, in some cases, widening the wage gap may be a necessary condition for boosting economic activity and human capital accumulation. However, this investment might not drive down wage inequality and could raise concerns about household debt.
Keywords: Household debt; student loans; capacity utilization; human capital; E12; E22; E24